Apology strategies in Malay among Malaysian university students / Nasiha Nasrudin - Nasiha , Nasrudin (2018)
This dissertation reports on a study that was carried out to describe the apology strategies utilized by Malaysian university students in the Malay language in six apology situations. For this purpose, data were elicited from 40 Malaysian university students through a Discourse completion tasks questionnaire. The participants were of the same language proficiency. Results of the study showed certain strategies appear more frequent than the others and that context plays an important role in the choices of apology strategies used. Other than that, they are more inclined towards the positive politeness, and they remain ‘polite’ in the sense they try to be courteous. The findings of this study might be of pedagogical help and significance to teachers, students and those interested in pragmatics in general and apology speech act in particular.